Markers of Bone Turnover in the Evaluation of Diagnosis and Prognosis of Multiple Myeloma in a Sample of Iraqi Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Subjects /This study is aimed to evaluate the bone resorption marker CTX, B-CTX, and bone formationmarker Osteocalcin in relation to the clinical presentation as well as to investigate the evidences of theosteoporotic processes by assessing osteoclast bone markers in the different stages of MM patients andcomparing these markers- in relation to standard prognostic markers in sample of MM Iraqi patients. – inaddition to interpretation of soluble CD138 in relation to prognosis.Methods/Sixty-five MM (males=41, females=24) patients distributed to different hematology centers inIraq were enrolled in this cross-sectional study.Their age range was 39-81 years, twelve of them were newlydiagnosed and the others were under treatment and distributed all on three stages from the disease accordingto the international staging system (ISS) : Group A – Stage I (n=21 patients, age mean 57.14±12.25 years),Group B – Stage II (n= 22 patients, age mean of 56.45±11.33 years), and Group C-Stage III (n=22 patients,age mean 60.59±11.55 years). Seven milliliters of venous blood samples were taken from each patient justprior to starting the chemotherapy for the measurement of blood hemoglobin (Hb), serum Creatinine, ,Calcium , Beat 2 Microglubulin Osteocalcin (OC), Total and Beta C-terminal telopeptide (CTX, BCTX),Parathyroid hormone (PTH), Syndecan-1 (CD138), and both kappa & lambda Free light chain (FLC?,FLC?).Results/Anemia was a general feature of all patients, with a gradual rise (from stage 1 to 3) in the concentrationsof creatinine and B2M P=<0.001, calcium P=0.01 and, all other studied markers CTX, BCTX, CD138,FLC? and FLC? has significant elevation in comparison among studied groups P=<0.001 with the exceptionof Osteocalcin ,which showed a general reduction.Conclusion/Multiple Myeloma patients have increased in bone remodeling throughout the disease coursewith progressive increment in relation to disease stage --. Plasma cells in MM leads to disturbance inexpression and secretion of CD138 in association with disease advancement.